The Relationship between Mother's Behavior and The Incident of Early Childhood Caries (ECC) - Aldilawati, Sari; Arifin, Nur Fadhilah; Syam, Syamsiah; A, Erna Irawati; Asyfa, Nur (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
General health is influenced by dental and oral health, which is an essential component of it. Toddlers experience tooth decay more quickly than adults do. This is because the enamel on freshly erupted teeth is still developing and is, therefore, more prone to caries. Aside from that, another common poor habit is parents ignoring their kids' bad habits by drinking irresponsibly and for extended periods from bottles. Early Childhood Caries is defined as having one or more teeth that are damaged (having cavities or not) and tooth loss on the surface of primary teeth caused by caries or fillings in children 71 months of age or younger. Children's oral and dental health is significantly influenced by the actions of their parents, particularly mothers. The state of mothers' and their children's oral health is significantly correlated. This study intends to ascertain if maternal conduct about preserving the dental health of her offspring and the frequency of Early Childhood Caries (ECC) is related. This study combines a cross-sectional analytical research design with a correlative descriptive research design. The Spearman correlation test is the statistical method employed. Maternal conduct and the preservation of children's dental health are significantly correlated, as indicated by the Spearman rank correlation test results, which had a p-value of 0.000, which is less than 0.05 (p-value <0.05). Based on the study's findings, it can be said that early childhood caries (ECC) incidence and a mother's behavior toward preserving her kids' oral health are related.